VISUALISASI KIAMAT MENUJU ESKATOLOGI AFTER LIFEStudi Analisis Penafsiran Surah al-Qari’ah Perspektif Ibn Ashur dalam al-Tahrir wa al-Tanwir - Khairul Atfal; Muhajirin (AL-BAYAN INSTITUTE, 2025)
This paper discusses Tafsir Maqashid in Tafsir al-Taḥrīr wa al-Tanwīr. This is based on 'Izz al-Dīn ibn Sa'īd in Ummahāt Maqāṣid al-Qur'ān wa Turuq Ma'rifatihā wa Maqāṣidiha who noted that Ibn Āshūr became one of the figures in the field of maqaṣid. So this paper wants to examine whether Ibn Āshūr also did maqāṣid when interpreting surah al-Qāri'ah. The descriptive-analytical approach used in this research yields the result that when Ibn Āshūr interpreted surah al-Qāri'ah, he was not much different from other commentaries that explain the linguistic discourse in it.